2014
DOI: 10.1016/j.oraloncology.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk genes in head and neck cancer: A systematic review and meta-analysis of last 5years

Abstract: El Repositorio Digital de la Universidad Nacional de Córdoba (RDU), es un espacio donde se almacena, organiza, preserva, prov ee acceso libre y procura dar visibilidad a nivel nacional e internacional, a la producción científica, académica y cultural en formato digital , generada por los integrantes de la comunidad universitaria. RISK GENES IN HEAD AND NECK CANCER: A SYSTEMATIC REVIEW AND META-ANALYSIS OF LAST 5 YEARSBrunotto Cita del documento:Brunotto, M, Zarate, A.M, Bono, A, Barra, J.L, Berra, S. Risk gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
1
38
0
3
Order By: Relevance
“…Molecular alterations are starting to directly affect the approach to patient care and are currently the subject of investigation in numerous clinical trials [15,16]. We wanted to explore the potential efficacy of implementing higher throughput strategies that combine targeted differential gene expression mutation profiling to help improve stratification of SCCHN by risk categories for both HPV-positive and negative disease.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular alterations are starting to directly affect the approach to patient care and are currently the subject of investigation in numerous clinical trials [15,16]. We wanted to explore the potential efficacy of implementing higher throughput strategies that combine targeted differential gene expression mutation profiling to help improve stratification of SCCHN by risk categories for both HPV-positive and negative disease.…”
Section: Introductionmentioning
confidence: 99%
“…The transcribed proteins for the polymorphisms have been shown to be different, structurally by electrophoretic mobility assay and functionally in vitro, with the p53 (Pro\Pro) variant protein being a stronger inducer of transcription and showing slower kinetics in inducing apoptosis than the p53 (Arg) genotype, and with the p53 (Arg) type also suppressing transformation of primary cells to a greater degree than the p53 (Pro) type 55 . However, our own recent study in relation to SNP and risk head and neck cancer reported no significant association with TP53 8 . At the level of epidemiological studies in various cancers, the association of this polymorphism with cancer is controversial and there is scant literature on this in relation to oral cancer 56 .…”
Section: Discussionmentioning
confidence: 66%
“…It also enables stronger and more generalized conclusions for identifying some models of risk markers that predict risks of oral cáncer and/or tumor progression, in order to improve prevention, early detection (mainly in patients with OPMD) and treatment [4][5][6][7] . In a previous work about the association of single nucleotide polymorphisms (SNP) in head and neck cancer, we showed that people considered at risk of developing head and neck carcinomas have an increase of gene polymorphism expression related to inflammation, carcinogenic metabolism, the stabilization and repair of the cellular genome, regulation of proliferation and/or apoptosis 8 . The main question is if SNPs associated with oral cancer are present in patients with OPMD.…”
Section: Introductionmentioning
confidence: 99%
“…Siendo el cáncer y la enfermedad celíaca patologías complejas no transmisibles, y su incidencia está altamente relacionada a determinantes sociales de la salud como son los socio-económicos y culturales. [4][5] Dentro de los trabajos recientes que hemos publicado en estas áreas se encuentran los estudios Prevención y diagnóstico temprano de enfermedades complejas no transmisibles: Un objetivo a lograr en Salud Pública.…”
Section: Editorialunclassified
“…4 En relación a los cánceres y/o desórdenes potencialmente malignos orales hemos avanzado en la determinación de modelos de riesgo identificando polimorfismos genéticos de riesgo en la población como son los relacionados al metabolismo del tabaco, a procesos inflamatorios, a los procesos de estabilidad del RNA mensajero y de mutaciones de genes relacionados a la reparación del genoma, mientras que dentro de los polimorfismos con un efecto protector sobre el desarrollo de estas patologías malignas y pre-malignas, se mencionan los polimorfismos relacionados al metabolismo de alcohol y a la reparación del DNA. 5 Las conclusiones más relevantes de nuestro trabajo es que el trabajo interdisciplinario, de un equipo de profesionales de la salud pertenecientes a diversas áreas, permite un adecuado abordaje de las patologías complejas y que la mejor estrategia metodológica para las enfermedades complejas es el diagnóstico temprano y el monitoreo de grupos de riesgo y el seguimiento del cumplimiento de las terapias en pacientes diagnosticados.…”
Section: Editorialunclassified